Fabrication and experimental characterization of a sol–gel derived nanostructured n-ZnO/p-Si heterojunction diode - Singh S.K.; Hazra P.; Tripathi S.; Chakrabarti P. (My University, 2025)
In this paper, fabrication and characterization of a sol–gel derived n-ZnO nanoparticle/p-Si heterojunction diode has been presented. A strong diffraction peak (002) obtained from XRD spectra of sol–gel derived ZnO thin film indicates that the growth of hexagonal wurtzite ZnO nanoparticles are preferably along the c-axis. The surface morphological features extracted from AFM and SEM images predict the uniform growth of ZnO nanoparticles over the p-Si substrate. The optical properties of ZnO nanoparticles have been measured in the spectral range of 300–1000 nm using ellipsometer and photoluminescence spectroscopy. The optical transmittance of ZnO nanoparticles has been observed between 81 and 92.66 % in visible region and the optical band gap has been found out to be 3.24 eV. Finally, metallic contacts were deposited on top of ZnO layer and bottom of Si layer to perform electrical characterization of nanostructured n-ZnO/p-Si heterojunction diodes. Electrical parameters including reverse saturation current, ideality factor, barrier height, rectification ratio have been calculated to explore the potential of the device for futuristic nanoelectronic and optoelectronic device applications. © 2015, Springer Science+Business Media New York.